Unfinished : The Anthropology of Becoming - Locke, Peter Andrew, 1979-; Biehl, João Guilherme (Book collections on Project MUSE., 2017)
The contributors to Unfinished explore the ethnographic essay's expressive potentials by pursuing an anthropology of becoming, which attends to the contingency of lived experience and provides new means to represent what life means and how it can be represented.